2015
DOI: 10.4317/jced.52693
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of dentist's intervention in smoking cessation: A review

Abstract: IntroductionSmoking is one of the main public health problems in developed countries. Despite extensive evidence on the effects of smoking on both oral and general health, the rate of smoking cessation is not promising.Material and MethodsTo review the evidence on knowledge and programs for smoking cessation developed by dentists, a literature review was carried out on programs for smoking cessation from the dentist’s perspective, as well as a review of behavioral guidelines that have been recently proposed fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 33 publications
2
35
0
Order By: Relevance
“…The increased use of e-cigarettes in recent years is controversial as it is unclear if they result in tobacco cessation 11. Smoking cessation interventions delivered by dental teams are seen to be effective in studies 45. Few studies examine effectiveness of smoking cessation intervention in head and neck cancer survivors specifically.…”
Section: How To Support Patients?mentioning
confidence: 99%
“…The increased use of e-cigarettes in recent years is controversial as it is unclear if they result in tobacco cessation 11. Smoking cessation interventions delivered by dental teams are seen to be effective in studies 45. Few studies examine effectiveness of smoking cessation intervention in head and neck cancer survivors specifically.…”
Section: How To Support Patients?mentioning
confidence: 99%
“…Previous research found that smoking dentists are less likely to be engaged in tobacco cessation. In the last 15-20 years more studies have been conducted to address the role of dentists in preventing smoking and encouraging patients to quit 11 . Studies that investigated this aspect of dental practice also aimed at understanding the barriers that may impede this vital role of dentists.…”
Section: Introductionmentioning
confidence: 99%
“…It therefore seems prudent to target young adult non-smokers in initiating the habit and to help quit smokers who have only recently taken up the habit. Authors confirm that quitting smoking helps reduce the risk of oral cancer by 50% in five years 8 and reduction of up to 12% in the number of cases of the destructive periodontal disease. 9 Owing to this significant impact on both oral and periodontal health, this study is aimed at reviewing the impact of tobacco use on periodontal tissues, the impact of smoking cessation to improve periodontal health and to benefit from the results of periodontal treatment.…”
Section: Introductionmentioning
confidence: 83%